Analysis of Filtration Efficiency of Activated Carbon Coated Sand Beds - Singh, Geeta; Sahajpal, Ishan (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 5 No 4 (2018): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Sourcing the clean water has remained of the great importance ever since the civilisation has come into the existence. Continuous efforts are being made to find out the innovative methods and techniques to treat water efficiently and economically. In this study, an attempt is made to make efficient water filter, to be used at large scale in water treatment plants, economically and commercially viable. It is made from activated carbon coated sand acquired from thermal degradation of sugar on river sand particles. The carbon coated sand is activated by chemical treatment. It is found that filter function satisfactorily in removing the TDS and dissolved organics from polluted water. The high concentration of carbon on sand have better adsorption power (15% sugar on sand is better than 5% sugar in sand) and higher the number of passes through filter facilitate the better results. Though â€œordinary sandâ€ used in conventional systems is good in removing organics but do not removes inorganic dissolved particles. It also could be done by this type of filters. Higher amount of chemicals used in every sector reach back to the prime sources of water. Which requires to be â€œre-treatedâ€ by water treatment plants. Thus, it becomes a necessity to find out innovative techniques to treat water. How to cite this article: Singh G, Sahajpal I. Analysis of Filtration Efficiency of Activated Carbon Coated Sand Beds. J Adv Res Alt Energ Env Eco 2018; 5(4): 1-5. DOI: https://doi.org/10.24321/2455.3093.201801